To Evaluate the Relationship between Overweight/Obesity Status, Sugar Consumption, and Dental Caries among 12–15-year-old School Children of Moradabad City - Supurna Pandit; Pradeep Tangade; Jeevan Josh; Sanchit Pradhan; Mohnish Muchhal; Aditya Veer Singh (Journal of Indian Association of Public Health Dentistry)
Background: Childhood is alluring phase of everybody’s life. Sugar intake play an key role in dental caries. Childhood obesity leads to adolescent obesity if we do not change the habits and the lifestyle of a child. Aim: This study aims to evaluate the relationship between overweight/obesity status, sugar consumption and dental caries among 12–15-year-old school children of Moradabad city. Setting and Design: The cross-sectional study was undertaken in various schools of Moradabad city using random sampling. Materials and Methods: The study was conducted on the 600 school-going kids of 12–15-year of the Moradabad city. Questionnaire was given to the school-going children to record their sugar consumption and their oral hygiene practice to record dentition status World Health Organization Oral health Assessment form for Children, 2013 was used. Intra-examiner variability was controlled by calibration of investigator before conducting the examination. Statistical Analysis Used: The statistical analysis was done using SPSS Version 20 (IBM software released since 2015). ANOVA, post hoc test was used. Results: Examination of 600 school-going kids was done. It was found that boys were more likely to have caries as compared to girls (Odds ratio [OR] =1.92, confidence interval [CI] =1.15–3.45). Similarly, overweight / obese children had 3.54 times higher chance of having carious than low/normal-weight children (CI = 1.83–7.26). Children with more than once a day sugar consumption had higher chance of caries than who consumed once per day (OR = 3.23, CI = 1.20–7.92). Conclusion: There was a significant association between overweight / obesity and caries experience among school children of 12–15 years of Moradabad city. Obesity and dental caries have common risk determinants and require a comprehensive multidisciplinary approach to pediatric patients by both medical and dental healthcare professionals.